2022
DOI: 10.1007/s00784-022-04538-2
|View full text |Cite
|
Sign up to set email alerts
|

Tooth agenesis in German orthodontic patients with non-syndromic craniofacial disorder: a retrospective evaluation of panoramic radiographs

Abstract: Objectives The study objective was to evaluate the tooth agenesis in German orthodontic patients with non-syndromic cleft lip and/or palate and Robin sequence compared to a control group without craniofacial disorder. Materials/methods A total of 108 panoramic radiographs were examined using the binary system of Tooth Agenesis Code (TAC) (excluding the third molar). Patients were divided into the craniofacial disorder group 1 (n = 43) and the healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
1
2
0
2
Order By: Relevance
“…In the current study, the location of the canines was assessed using visual diagnosis of the examiners without an exact standardized scaling of the PAN. In a previous study, tooth agenesis of patients with CL/P or RS were assessed by the same two examiners, and comparably to the current study, the kappa value showed a moderate degree of agreement [ 48 ]. This study was performed under the same conditions as the current one.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the current study, the location of the canines was assessed using visual diagnosis of the examiners without an exact standardized scaling of the PAN. In a previous study, tooth agenesis of patients with CL/P or RS were assessed by the same two examiners, and comparably to the current study, the kappa value showed a moderate degree of agreement [ 48 ]. This study was performed under the same conditions as the current one.…”
Section: Discussionsupporting
confidence: 55%
“…Generally, in this study cleft-sided canines have shown a higher risk for dislocation and malposition compared to the non-cleft-sided ones. Not only this latter has to be considered in orthodontic treatment of patients with CD, also the correlation with tooth agenesis [ 48 ]. Several authors described that displacement and impaction coincide with tooth agenesis, specifically regarding the lateral incisor [ 21 , 45 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining radiographic assessed parameters had moderate degrees of agreement for both examiners. Compared to a study about evaluation of the tooth agenesis of patients with CL/P or RS assessed by the same two examiners, like in the current study, the kappa value showed a moderate degree of agreement, likewise [52]. This study was performed under the same conditions as the current one.…”
Section: Discussionmentioning
confidence: 44%
“…TAC를 이용하면 결손이 된 치아의 번호를 일렬로 나열하 지 않아도 한 분악 내 어떤 치아가 결손이 되었는지 알 수 있으 며, 4분악의 TAC값을 함께 나타내면 전악에서 결손된 모든 치 아를 한 번에 나타낼 수 있다. 이를 응용하면 상-하악 및 악궁 전체에서 빈번하게 함께 결손이 되는 치아의 유형을 알 수 있다 [4,5,8,14].…”
Section: 서론unclassified
“…TAC를 이용하면 결손이 된 치아들을 하나의 숫자로 나타낼 수 있을 뿐 만 아니라, 특정 유전자 변이를 가진 환자들의 공통된 TAC값은 그 유전자 변이와 관련된 표현형으로 생각할 수 있다 [5]. 이 사 실을 기반으로, 최근에는 TAC를 이용하여 구순 구개열 환자들 의 영구치 결손 유형을 분류하는 연구가 행해지고 있다 [14,15]. [18].…”
Section: 서론unclassified